Diagnostic and Clinical Characteristics of Ectopic Pregnancy: A Retrospective Audit in a UK Early Pregnancy Unit - Mena Abdalla (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Background: Ectopic pregnancy remains a leading cause of maternal morbidity and mortality in the first trimester. Early and accurate diagnosis through ultrasound examination is crucial for optimal patient outcomes. Objective: To analyze the demographic characteristics, clinical presentation, ultrasound findings, and diagnostic patterns of ectopic pregnancies managed in an Early Pregnancy Unit (EPU) over a one-year period. Methods: A retrospective clinical audit was conducted on 140 consecutive cases of ectopic pregnancy diagnosed and managed at the Princess Royal University Hospital EPU during 2020. Data were extracted from ultrasound reports and clinical records, including patient demographics, gestational age at presentation, ultrasound findings, ectopic location, and mass characteristics. Statistical analysis was performed using SPSS version 28.0, with descriptive statistics, chi-square tests, and correlation analysis where appropriate. Results: The mean maternal age was 31.9 ± 5.3 years (range 21-44 years), with the highest incidence in the 30-34 years age group 44 (31.9%). Mean gestational age at presentation was 6.4 ± 2.0 weeks. Fallopian tube involvement accounted for 91 (89.2%) of cases, with 49 (48.0%) in the right tube and 42 (41.2%) in the left tube. Ovarian ectopic pregnancies comprised 8 (7.8%) of cases. The mean ectopic mass size was 22.6 ± 11.8 mm (range 3-80 mm). Ultrasound visualization of ectopic gestational structures varied, with gestational sacs visible in 34 cases, yolk sacs in 12 cases, and embryonic structures in 9 cases. Conclusion: This audit demonstrates the typical demographic and clinical patterns of ectopic pregnancy in a UK EPU setting. The findings support the importance of early ultrasound assessment and highlight the predominance of tubal ectopic pregnancies. These data contribute to quality improvement initiatives and provide benchmarks for EPU services.